A pairing-based password authentication scheme using smart card with user anonymity. (2015) - Jiang, Linmei; Dai, Songsong; Liu, Niansheng; Guo, Donghui
Password authentication is one of the most convenient and frequently used mechanisms to provide secure remote access control. In this paper, a pairing-based password authentication scheme which draws on the experience of two previous researches is proposed, and the detailed authentication phases which utilise the good properties of bilinear pairing are illustrated. Meanwhile, strict cryptanalysis is made to clarify the good security and functionality features of the proposed scheme in defending various attacks. Besides that, some flaws of a previous scheme are analysed and theoretical comparison of the computation cost with that scheme is made. Furthermore, experiments are conducted properly and the results are shown to explain the high efficiency of the proposed scheme.